Identification of Novel Bacteria by Using 16S rRNA from Clinical and Soil Samples - Enas A. Bady; Sabaa Ali Mohammed Al-Fadal; Rafeef Amer Abdul-Jabar; Dheyaa B. Al-Rubeai (Institute of Medico-legal Publications Pvt Ltd, 2021)
The 16S rRNA gene is a useful tool and molecular indication for identifying novel bacterial species fromdifferent sources. It is widespread for members of this field and thanks to the continuous expansion ofinformation sequence databases. We isolated Gram-negative and Gram-positive bacilli from the respiratoryinfections and soil respectively, and phenotypical and molecular identifications were performed. Geneticanalysis indicated that the isolated bacteria were a new species belonging to Bacterium strain and Proteus sp.Bacterium strain JND-RSIb-21A with Accession number MW013547.1 which closely related (99.8%) withBacillus subtilis strain JND-RSIb-21A for its Transversion point mutation (G instead of C) at the position445 bp. Proteus sp. strain AMJ131 with Accession number MW015095.1 the isolate related closely (99.8%)to Proteus mirabilis strain AMJ131for two-point mutations Transition of (G instead of T) and Transversionof (T instead of A) at position 9bp and 10bp respectively